THE ROLE OF VERTICAL HOLINESS IN THE MULTI-STOREY INFRASTRUCTURE DESIGN - I Wayan Redana; Putu Alit Suthanaya; Ngakan Made Anom Wiryasa; I Made Sastra Wibawa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
The increasing number of residents demands the provision of settlement facilities and infrastructure. Limited land is an obstacle to the development in the horizontal direction, especially the use of green open land which will cause land conversion. The limitation of the building height regulated by local regulations, as well as the local wisdom, namely vertical holiness can be a challenge related to the idea of building multi-storey buildings. When you want to enter the lower floors of the building, there is a feeling of doubt because there are other residents on the upper floors who step over. This study aims to reveal the relationship of vertical holiness with multi-storey building design and formulate vertical holiness as an effort to implement it in a design so that it can be accepted by the community. This study uses a methodology to examine the problem by interviewing the stakeholders and filling out the questionnaire, therefore, the relationship between vertical holiness and multi-storey building design can be obtained. The results of the study clearly confirm that there is indeed a correlation between vertical holiness and multi-storey building design. Thus, the design should pay attention to this vertical holiness. The study also encourages that the formulation of vertical holiness should be legally stated in regulation so that it is easily understood and accepted by the community.